2013
DOI: 10.1007/s00247-012-2611-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vertical positioning on organ dose, image noise and contrast in pediatric chest CT—phantom study

Abstract: Vertical off-centering markedly affects organ doses and measured image-quality parameters in pediatric chest CT examination. Special attention should be given to correct patient centering when preparing patients for CT scans, especially when imaging children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 32 publications
5
38
1
Order By: Relevance
“…In order to calculate the dose estimation we evaluated the location of glandular breast tissue in a large patient cohort. In contrast to the study by Taylor et al, in which measurements were performed in relation to the centre of the gantry, we eliminated the frequent bias effect of improper patient centring [10,11] by virtually equating the isocentre of the gantry and the anatomical isocentre at the level of the carina. Thus we were able to calculate the theoretically possible dose reduction assuming a perfect centring of the patient in the gantry.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In order to calculate the dose estimation we evaluated the location of glandular breast tissue in a large patient cohort. In contrast to the study by Taylor et al, in which measurements were performed in relation to the centre of the gantry, we eliminated the frequent bias effect of improper patient centring [10,11] by virtually equating the isocentre of the gantry and the anatomical isocentre at the level of the carina. Thus we were able to calculate the theoretically possible dose reduction assuming a perfect centring of the patient in the gantry.…”
Section: Discussionmentioning
confidence: 90%
“…The tube current modulation of OBTCM works in relation to the isocentre of the gantry. However, former studies showed that patient miscentring is a common problem [10,11] and patients are often centred too low in the gantry. In this case, a shift of breast tissue into the increased dose zone occurs resulting in a higher exposure to the breast.…”
Section: Scan Protocolmentioning
confidence: 98%
“…An exception was the eye lens, where the CT-Expo value of 60.6 mGy was higher than the measured mean value of 54.4 mGy. CT Expo values were lower however, for the breast (2.7 mGy vs 4.0 mGy) and thyroid Kaasalainen et al (7) and Habibzadeh et al (5) . These studies showed that when the scanning object was aligned off-center, below the isocenter, there was an increase in dose at the upper surface and an increase in image noise at the lower half of the phantom.…”
Section: Resultsmentioning
confidence: 95%
“…Because the densities of soft tissue and brain tissue are very similar, only two peaks could be identified for our analysis volume: one for soft/brain tissue and the other for bone tissue. Noise was estimated by calculating the full width at the half maximum of the distribution of HU values around each of these peak values (for a more thorough discussion of the methodology, see [18]). Median filtering (nine successive values) was applied prior to the full width at the half maximum calculation.…”
Section: Estimation Of Image Noise and Contrastmentioning
confidence: 99%